Colors and Some Morphological Traits as Defensive Mechanisms in Anurans. (26th January 2009) - Toledo, Luís Felipe; Haddad, Célio F. B.
Abstract : Anurans may be brightly colored or completely cryptic. Generally, in the former situation, we are dealing with aposematism, and the latter is an example of camouflage. However, these are only simple views of what such colorations really mean and which defensive strategy is implied. For instance, a brightly colored frog may be part of a mimicry ring, which could be either Batesian, Müllerian, or Browerian. These are only examples of the diversity of color-usage systems as defensive strategies. Unfortunately, reports on the use of colors as defensive mechanisms are widespread in the available literature, and the possible functions are rarely mentioned. Therefore, we reviewed the literature and added new data to this subject. Then, we the use of colors (as defensive mechanism) into categories. Mimicry was divided into the subcategories camouflage, homotypy, and nondeceitful homotypy, and these groups were also subcategorized. Dissuasive coloration was divided into behavioral display of colors, polymorphism, and polyphenism. Aposematism was treated apart, but aposematic colorations may be present in other defensive strategies. Finally, we propose functions and forms of evolution for some color systems in post-metamorphic anurans and hope that this review can be the basis for future research, even on other animal groups.